Theories of Plates and Shells Critical Review and New Applications - Kienzler, Reinhold 1950-; Ott, Ingrid; Altenbach, Holm 1956- (Springer Berlin Heidelberg, 2004)
Plate and shell theories experienced a renaissance in recent years. The potentials of smart materials, the challenges of adaptive structures, the demands of thin-film technologies and more on the one hand and the availability of newly developed mathematical tools, the tremendous increase in computer facilities and the improvement of commercial software packages on the other caused a reanimation of the scientific interest. In the present book the contributions of the participants of the EUROMECH Colloquium 444 "Critical Review of the Theories of Plates and Shells and New Applications" have been collected. The aim was to discuss the common roots of different plate and shell approaches, to review the current state of the art, and to develop future lines of research. Contributions were written by scientists with civil and mechanical engineering as well as mathematical and physical background
Keywords: Engineering; Structural Mechanics; Continuum Mechanics and Mechanics of Materials; Continuum mechanics; Structural mechanics